An analysis of wire-cut parameters in electric-discharge of titanium alloys - Nehadabed, Farook; Sapit, Azwan; Kariemshather, Saad (Transstellar Journal Publications and Research Consultancy Private Limited (TJPRC PVT. LTD.), 2019)
The present paper, focuses on wire electric dis-charge machine of titanium alloys. It can be considered as an attempt to develop two models of response variables, they are; the operating rate, the surface-roughness, and the rate of material removing, In the wire electric dis-charge machine process using the response surface methodology. The pilot plan is based on Minitab 18, and the analysis convey the major six parameters. ANOVA was applied to determine the importance of the advanced model, the test results confirm the validity and suitability of the advanced RSM-model. Lastly, the optimum parameter settings is improved.